Real‐time correction of ERA‐Interim monthly rainfall. Issue 14 (19th July 2013) - Di Giuseppe, Francesca; Molteni, Franco; Dutra, Emanuel
<x xml:space="preserve">Abstract</x> [1] Gridded precipitation from reanalysis can be a valid proxy for observations in many regions where local measurements are not available. Despite the continuous improvements in assimilation systems and the growing availability of in situ and remote observations, model errors can nevertheless still affect reanalysis quality. A temporal and spatial correction of ERA‐Interim rainfall monthly means is proposed. It is shown that the strategy of postprocessing the data set is crucial for drought monitoring and forecasting.